Severe depression association with the addiction to fast food and smartphones in Jordanians: a cross-sectional study - Nawal AlSakarneh; Dana Kakeesh; Khaled Al-Marazeeq; Ali Ahmad Banysaed; Omar Gammoh (Discover Food)
Abstract Background The connection between psychiatry health, mental health, and lifestyle is under-studied in the Arab world. This study examined whether addictions to smartphones and fast food are associated with severe depressive symptoms in a cohort of Arab Jordanians. Method This research is cross-sectional. The Patient Health Questionnaire-9 was used to measure the severity of depression (PHQ-9), food addiction was assessed using the 9-item Modified Yale Food Addiction Scale (mYFAS), and smartphone addiction was assessed using the Arabic-validated Smartphone Addiction Scale. Using multivariable binary logistic regression, the relationship between food addiction, and depressive symptoms. Results: Data were analyzed from 426 participants, 264 participants (62.0%) reported being addicted to smartphones, and 156 (36.6%) reported severe depressive symptoms. The multivariable binary logistic regression revealed that severe depression was significantly associated with lower income (OR = 2.14, 95% Cl 1.34–3.41, P = 0.001), addiction to smartphones (OR = 2.15, 95% = 1.39–3.32, P = 0.001), and increased addiction to fast food (OR = 1.06, 95% = 1.04–1.08, P =  < 0.001). Conclusion Addiction to smartphones, addiction to fast food, and low income were all associated with severe depression in Arab Jordanians, community awareness is highly required to adopt a healthy lifestyle.